Distance Learning in Russian Schools during the COVID-19 Pandemic: Predicting Student Outcomes - Natalia Isaeva; Anna Kobtseva; Marina Tsatrian (Voprosy obrazovaniya / Educational Studies Moscow, 2024)
The outburst of COVID had a major impact on the lives of people all over the world. While educational systems were developing plans, preparing teachers and schools for transition to distance learning, students were left in the situation which required them to organize their studies by themselves. This paper attempts to identify predictors of student learning outcomes, namely, students’ self-rated achievements, learning effort, and emotions, during the lockdown based on the data derived via the School Barometer survey in Russia. A total of 22080 students from 85 Russian regions participated in the survey. Relative weight analysis found statistically significant predictors for students’ learning outcomes: ‘learning effort’ and ‘negative emotions’’. The paper addresses such issues as student autonomy, teaching practices, and access to education.